2019
DOI: 10.18542/raf.v12i2.5549
|View full text |Cite
|
Sign up to set email alerts
|

Jovens rurais estudantes da Escola Estadual Jaraguá, Água Boa (MT): projetos de vida, dilemas e sucessão familiar

Abstract: Este trabalho buscou aprofundar as questões relacionadas aos projetos de vida dos jovens rurais, estudantes do Curso Técnico em Agroecologia da Escola Estadual Jaraguá, município de Água Boa (MT), sob a perspectiva de sucessão familiar. Isso envolve os aspectos na sua formação e objetiva verificar quais são seus projetos de vida e sua relação com a sucessão familiar. A metodologia utilizada foi a aplicação de questionários a 14 estudantes do curso técnico em Agroecologia. Concluímos na pesquisa que a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
2
1
5
Order By: Relevance
“…In a study by Maia et al (2019), in which they evaluated life projects of young students of a technical course in Agroecology integrated to high school, at a school located in the municipality of Água Boa (MT), the authors observed a higher percentage of male students, showing that women represented the minority of the interviewed students, a scenario different from that observed in the present study. According to Figure 6, a large portion of respondents have completed high school (84%), with 8% having incomplete higher education, percentages that include most of those who already work professionally in the sector (Figure 7A).…”
Section: Resultscontrasting
confidence: 95%
See 2 more Smart Citations
“…In a study by Maia et al (2019), in which they evaluated life projects of young students of a technical course in Agroecology integrated to high school, at a school located in the municipality of Água Boa (MT), the authors observed a higher percentage of male students, showing that women represented the minority of the interviewed students, a scenario different from that observed in the present study. According to Figure 6, a large portion of respondents have completed high school (84%), with 8% having incomplete higher education, percentages that include most of those who already work professionally in the sector (Figure 7A).…”
Section: Resultscontrasting
confidence: 95%
“…(Figure 4). According to Silva, et al (2019) the use of solar panels to feed of electric fences in the coastal region of the state of Pernambuco, showed high efficiency in meeting the technical needs required for the proper handling of animals grazing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Por isso é de grande ênfase o uso da conscientização para que as famílias passem para seus descendentes o uso das técnicas agroecológicas para preservação dos recursos naturais. Sendo que o processo de formação de novas gerações é um dos fatores principais que contribui para a existência da unidade familiar, e de possíveis processos que valorizem a utilização de práticas alternativas à produção, como é o caso do desenvolvimento da produção agroecológica em áreas caracterizadas pelo longo histórico de degradação do ambiente (MAIA et al, 2018).…”
Section: Resultsunclassified
“…Segundo Maia et al [14] essa sucessão pode ser determinada pela ausência tanto de perspectivas sobre renda quanto pela participação dos jovens nas decisões familiares, fazendo com que a migração para a cidade acabe sendo uma das alternativas para conseguir autonomia/independências dos pais. Os autores também afirmam que a vivência desde muito cedo no campo e os estímulos dos pais são elos importantes que determinam em muitos casos a permanência ou prazer dos filhos(as) pela atividade agrícola.…”
Section: Discussionunclassified